Creative Tourism Model Development through Local Participation: A Case Study of Lan Khoi Sub-district, Pa-Phayom District, Patthalung Province - Pattano, Duangtida; Sae Wong, Jarinee (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2018)
The purposes of this research were 1) to study tourism resources and local wisdom related to tourism potential of Lan Khoi Sub-district, Pa-Phayom District, Phatthalung province, Thailand; 2) to develop creative tourism model based on local participation; and 3) to create tourism routes for creative tourism within the area. This research was qualitative in nature. Data were collected using interview, group conversation, community survey, and group discussion with representatives from government organizations, Lan Khoi Municipality, tourism entrepreneurs, local leaders, local occupational groups, and local people. Results revealed that Lan Khoi’s tourism resources are abundant and can be classified into four categories: history of the community; traditions and festivals conducive to tourism; local products for tourists; and wonderful tourism attractions. In terms of the local wisdom for occupations, it was found that no practices were transferred to the new generation. With regard to the development of creative tourism model in Lan Khoi, tourism attractions, housewife groups, occupational groups could be of great use, and the emphasis should be placed on tourism activities through learning and giving them a trial. For example, the weaving of Lan Khoi cloth, making shadow puppets, and getting to learn about local herbs. Ultimately, these activities would generate tourist interactions with local people and the tourists would be ableto gain authentic experiences. Finally, three linking routes leading to various tourism attractions were constructed. The routes are expected to provide easy access to tourism attractions and enhance tourists’ involvement in all kinds of creative tourism activities.